Semi-markov models : control of restorable systems with latent failures - Obzherin, Yuriy E.; Boyko, Elena G. (London : Academic Press, 2015)
Featuring previously unpublished results, Semi-Markov Models: Control of Restorable Systems with Latent Failures describes valuable methodology which can be used by readers to build mathematical models of a wide class of systems for various applications. In particular, this information can be applied to build models of reliability, queuing systems, and technical control. Beginning with a brief introduction to the area, the book covers semi-Markov models for different control strategies in one-component systems, defining their stationary characteristics of reliability and efficiency, and uti.
3.5.1 -- System Description.
Includes bibliographical references and index.
Online resource; title from PDF title page (ScienceDirect, viewed February 16, 2015).
Keywords: System analysis -- Mathematical models; Markov processes; SCIENCE -- System Theory; TECHNOLOGY & ENGINEERING -- Operations Research; Markov processes; System analysis -- Mathematical models; Electronic books; Electronic books